A SURVEY SURVEY ON ISOLATION TECHNIQUES USED BY ENDODONTISTS AND GENERAL DENTISTS - James, Dr. Vandana; Balagopal, Dr. Sundaresan; J., Varshinee.G.; Varghese, Dr. Sunil Chandy; I, Vaishnavi.; V., Manishaa. (Journal of Biomedical and Pharmaceutical Research, 2019)
Aim: To determine the most preferred and used isolation technique by Endodontists and General Dentists during their treatment. To see whether choice of isolation technique differs among Endodontists and General Dentists. Materials and Methods: A preformed questionnaire was provided to the Endodontists and General Dentists regarding usage of isolation techniques in their practice. Informed consent was obtained from the dentists before answering the questionnaire. STATISTICAL ANALYSIS USED: Analyses were done using SPSS. The main outcomes of interest were the frequency of use of different types of isolation techniques, with attitudes as the key predictors. Scores were used to examine the relationship between the dentist’s attitudes about isolation techniques and whether these techniques were used. Results: The most commonly preferred isolation technique is found to be rubber dam and the choice of isolation technique differed among Endodontists and General Dentists, Endodontists most commonly using rubber dam than General Dentists who preferred using cotton rolls. Conclusion: From this survey we can conclude that Endodontists mostly prefer using rubber dam due to their increased knowledge about the isolation technique. Knowledge among General Dentists about rubber dam has to be increased. Keywords: Isolation technique, Rubber dam, Endodontists, General dentists.